VALUATION AND FINANCING OF COTTON PROCESSING PLANTS - Tolegen, Aigerim; Uskenbayev, Azamat; Ablezov, Bauyrzhan; Koshanova, Nassipzhan (Nazarbayev University, Graduate School of Business, 2019)
This thesis is dedicated to the valuation and financing of cotton processing plants in South Kazakhstan. The project is fully analyzed using situational analysis. For valuation DCF approach was used as per internal procedures of BV Management Company, which provides investment funding for firms under venture agreement. The project aim is to raise additional financing that is required to supplement working capital.
Keywords: Type of access: Restricted; Cotton processing plants